White Matter Microstructure Alterations in Patients With Spinal Cord Injury Assessed by Diffusion Tensor Imaging - Guo, Yun; Gao, Feng; Liu, Yaou; Guo, Hua; Yu, Weiyong; Chen, Zhenbo; Yang, Mingliang; Du, Liangjie; Yang, Degang; Li, Jianjun (Frontiers in Human Neuroscience, 2019)
Compared to healthy controls, spinal cord injury (SCI) patients demonstrated white matter (WM) abnormalities in the brain. However, little progress has been made to compare whether cerebral WM differences between SCI-subgroups. The purpose of the study was to investigate WM mircrostructure differences between paraplegia and quadriplegia using tract-based spatial statistics (TBSS) and atlas-based analysis methods. Twenty-two SCI patients (11cervical SCI and 11 thoracic SCI) and 22 age- and sex-matched healthy controls were included in this study. TBSS and atlas-based analyses were performed between SCI and control groups and between SCI-subgroups using multiple diffusion metrics, including fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD). Compared to controls, SCI patients had decreased FA along with increased MD and RD in corpus callosum (genu and splenium), superior longitudinal fasciculus (SLF), corona radiata (CR), posterior thalamic radiation (PTR), right cingulum (cingulate gyrus) (CCG) and right superior fronto-occipital fasciculus (SFOF). Cervical SCI patients had lower FA and higher RD in left PTR than thoracic SCI patients. Time since injury had negative correlations with FA within right SFOF (r=-0.452, p=0.046) and positive association between the FA of left PTR and sensory score of ASIA (r=0.428, p=0.047). In conclusion, our study suggest that multiple cerebral WM tracts are damaged in SCI patients, and WM disruption in cervical SCI was worse than thoracic injury level, especially in the region of PTR.